Protection for the Right of Publicity in the Face of Deepfake Technology : Right of Publicity in the International Privacy and Property Protection Frameworks - Sirola, Noora (My University, 2023)
This thesis focuses on the right of publicity in the face of deepfake technology and asks the research question: Could international privacy and property protection frameworks be expanded to encompass right of publicity and would doing so provide sufficient protection for deepfakes in commercial context online? This thesis aims to answer this question by analysing to what extent the international privacy and property protection frameworks encompass the right of publicity when an artificial image of an individual is created using deepfake technology and the image is subsequently used in commercial context online without consent. With the rise of new technologies and artificial influencers these questions might need to be answered sooner than expected. This thesis aims to provide considerations to legislators and academics on the expansion of the right of publicity based on international privacy and property protection frameworks. It uses legal dogmatics, and the main source of international law is different treaties and conventions related to the human rights of privacy and property, especially the European Convention of Human Rights. Another main source is the case-law of the European Court of Human Rights, which forms the basis for the privacy and property protection frameworks presented in this thesis. It is concluded that both the international privacy and property protection frameworks can be expanded to encompass the right of publicity and doing so might provide more sufficient protection against deepfakes in commercial context online. The expansion of the right of publicity might, however, also create more inequality and censorship, and thus, the international community needs to carefully analyse what do we want our future to look like in this regard.

Tässä tutkielmassa tarkastellaan the right of publicity -käsitettä deepfake- eli syväväärrennössisältöjen näkökulmasta ja esitetään seuraava tutkimuskysymys: Voisiko kansainvälisiä yksityisyyden ja omaisuuden suojan kehyksiä laajentaa kattamaan the right of publicity -käsitteen, ja antaisiko se riittävää suojaa kaupallisessa tarkoituksessa käytettäviä syväväärennöksiä vastaan verkossa? Tutkielmassa pyritään vastaamaan tähän kysymykseen analysoimalla, missä määrin kansainväliset yksityisyyden ja omaisuuden suojaa koskevat säännökset kattavat the right of publicity -käsitteen silloin, kun henkilöstä luodaan syväväärennetty kuva ja kuvaa käytetään myöhemmin kaupallisessa tarkoituksessa verkossa ilman suostumusta. Teknologian kehittyessä tähän kysymykseen saatetaan joutua vastaamaan odotettua nopeammin. Tämän tutkielman tarkoituksena on herättää keskustelua lainsäätäjien ja tutkijoiden keskuudessa the right of publicity -käsitteen laajentamisesta kansainvälisten yksityisyyden ja omaisuuden suojan kehyksien pohjalta. Tutkielman ote on pääosin lainopillinen ja sen pääasiallisena lähteenä ovat erilaiset kansainväliset sopimukset koskien yksityisyyden ja omaisuuden suojaa, erityisesti Euroopan ihmisoikeussopimus. Toinen pääasiallinen lähde on Euroopan ihmisoikeustuomioistuimen ratkaisukäytäntö, joka muodostaa perustan tässä tutkielmassa esitetylle yksityisyyden ja omaisuuden suojan kehyksille. Tutkielmassa todetaan, että sekä yksityisyyden että omaisuuden suojan kansainvälisiä kehyksiä voitaisiin laajentaa siten, että ne kattavat the right of publicity -käsitteen, ja näin voitaisiin suojata paremmin henkilöitä kaupallisessa tarkoituksessa käytettäviä syväväärennöksiä vastaan verkossa. The right of publicity -käsitteen kehittäminen voisi kuitenkin myös lisätä eriarvioisuutta ja sensuuria, joten kansainvälisen yhteisön on pohdittava huolellisesti sitä, miltä haluamme, että tulevaisuus näyttää.
Keywords: international law, privacy protection, property protection, human rights, right of publicity, deepfake, technology